2017
DOI: 10.1016/j.foodcont.2016.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of perceived benefits and traceability system on the readiness for Halal Assurance System implementation among food manufacturers

Abstract: Despite consistent monitoring by the Department of Islamic Development Malaysia (JAKIM), the fabrication of fake halal logos and certificates by irresponsible parties continues to challenge the integrity and authenticity of halal products. Malaysia's Halal Certification Procedures (Second Revision, 2012) state that companies operating in Malaysia need to develop their Halal Assurance System (HAS) to strengthen the management of halalrelated matters within organizations. The purpose of this study is to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 60 publications
4
46
1
3
Order By: Relevance
“…Table 2 shows that perceived advantages and the size ‘medium’ were significant determinants of a stakeholder’s intention to join an FI-ISS. Perceived advantages or benefits were also positively related to traceability systems implementation and the readiness for the implementation of a halal assurance system, for example, among small and medium-sized enterprises (SMEs) in the study of Abd Rahman et al [22]. The dummy “medium size” is significant in the model with a negative coefficient, confirming that medium company size lowers the intention to join an FI-ISS.…”
Section: Resultsmentioning
confidence: 89%
“…Table 2 shows that perceived advantages and the size ‘medium’ were significant determinants of a stakeholder’s intention to join an FI-ISS. Perceived advantages or benefits were also positively related to traceability systems implementation and the readiness for the implementation of a halal assurance system, for example, among small and medium-sized enterprises (SMEs) in the study of Abd Rahman et al [22]. The dummy “medium size” is significant in the model with a negative coefficient, confirming that medium company size lowers the intention to join an FI-ISS.…”
Section: Resultsmentioning
confidence: 89%
“…The indirect and direct advantages from the adoption of IEBT can be seen in maximizing existing sources, and it can impact the profit. Numerous works by Abd Rahman et al (2017); Mehrtens et al (2001); Müller and Voig (2018) have reported that relative benefits are strong predictors of IEBT and related technologies in SMEs. Notably, the acceptance of IEBT by SMEs is seen from an innovation perspective.…”
Section: Adoption Of Internet and E-business Technologies (Iebt)mentioning
confidence: 99%
“…alāl compliance [73]. In a recent study, many areas for potential research in halāl assurance in the food industry have been identified, and critical issues have been highlighted [74]. Incorporating halāl features into the HACCP system could be a plausible tool for halāl assurance.…”
Section: Food Safety In H Alāl Assurancementioning
confidence: 99%
“…These standards could be contemplated by more than one hundred active certifying bodies, governmental or non-governmental organizations, for ḥalāl compliance [ 73 ]. In a recent study, many areas for potential research in halāl assurance in the food industry have been identified, and critical issues have been highlighted [ 74 ]. Incorporating halāl features into the HACCP system could be a plausible tool for halāl assurance.…”
Section: Food Safety In ḥAlāl Assurancementioning
confidence: 99%